2004
DOI: 10.1597/02-109.1
|View full text |Cite
|
Sign up to set email alerts
|

An Acoustic Study of the Temporal Characteristics of Nasalization in Children with and without Cleft Palate

Abstract: Nasalization, as reflected by acoustic signals, showed different timing characteristics between children with cleft palate and without cleft palate and across vowel contexts. This suggests that the duration of nasalization reflecting temporal patterns of the oral-nasal acoustic impedance may have an influence on the perception of hypernasality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 22 publications
7
32
0
Order By: Relevance
“…Also, the results in Forner ͑1983͒ revealed that the group with cleft palate produced longer plosive and affricate stop gaps. The results in Ha et al ͑2004͒ also suggest that children with cleft palate exhibit longer temporal durations of nasalization than normal children. Speakers with cleft palate might show developmental delay or deviance of speech motor control skill due to their anatomical differences in the structure of the palate.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Also, the results in Forner ͑1983͒ revealed that the group with cleft palate produced longer plosive and affricate stop gaps. The results in Ha et al ͑2004͒ also suggest that children with cleft palate exhibit longer temporal durations of nasalization than normal children. Speakers with cleft palate might show developmental delay or deviance of speech motor control skill due to their anatomical differences in the structure of the palate.…”
Section: Discussionmentioning
confidence: 73%
“…Nasal onset interval, nasal offset interval, and total nasalization duration, which reflect timing characteristics of nasalization, were measured on the basis of features revealed in the acoustic wave forms, spectrograms, and energy contours. The definition of timing measurements and the procedure used to obtain the measurements were identical to the ones described in Ha et al ͑2004͒. The timing measurements are defined in the following and displayed in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for some of the acoustic abnormalities described herein, especially the apparent relationship between severity of VPI and shimmer perturbation, may be that the individual is attempting to regulate subglottal pressure and vocal tract aerodynamics in a condition in which there is insufficient coupling between the resonant nasal cavities and the rest of the vocal tract [21], potentially increasing vocal noise.…”
Section: Discussionmentioning
confidence: 99%
“…In both languages, high vowels exhibited more assimilating nasality than low vowels characterized by longer duration of nasalization in high vowels (both proportionally and absolutely) than in low vowels. Consistent with Rochet and Rochet (1991) similar acoustic studies (Ha, Sim, Zhi & Kuehn, 2004;Ha & Kuehn, 2006) investigated the relationship between vowel height and the duration of nasalized portion of the resulting acoustic segment in the utterances of /pamap/, /pimip/, and /pumup/. Both studies reported longer duration for the nasal coarticulatory effect on high vowels compared to low vowels.…”
Section: Velopharyngeal Coarticulation and Vowel Heightsupporting
confidence: 58%